Uniqueness of solution of production control problem in a manufacturing system with degenerate demand - Baten, Md Azizul (Springer US, 2011)
This paper studies the production inventory problem of minimizing the expected discounted present value of production cost control in a manufacturing system with degenerate stochastic demand.We establish the existence of a unique solution of the Hamilton-Jacobi-Bellman (HJB) equation associated with this problem.The optimal control is given by a solution to the corresponding HJB equation.